A Study on Practical Activities That Promote Students’ Speaking Skill - Achekzai, Zarghona (Randwick International of Social Science Journal, 2025)
The aim of this article is a study of practical activities that promote students’ speaking skill. Through library research different practical speaking activities found that promote students’ speaking skill. Discussion is the main type of activity and the most frequently used activity in the speaking class. Dialogue is another type of activity which is used for language function practice such as suggesting, asking information, agreeing, apologizing, disagreeing, and greeting. It is found that simulation and role play can be used for inspiring general oral fluency or training students for specific situations. Debate is other kind of activity that provides a good opportunity for developing students’ speaking skills. In addition, Storytelling activities encourage student’s oral expression and increase overall language proficiency in speaking, listening comprehension, writing, and reading. To conduct surveys and questionnaires can be used for provoking conversation and opinion exchange. Moreover, for making the learners to speak, problems are good sources. To solve the problem students, have to use the language while engaged in the problem. Picture use is another activity that can be used in EFL classes and it is useful for learning that facilitated by imagery. Moreover, it is found that television, radio games and information-gap games motivate students to speak in speaking class.